Association between winter cold spells and acute myocardial infarction in Lithuania 2000–2015 - Vidmantas Vaičiulis (Nature Portfolio, 2021)
Abstract Acute myocardial infarction (AMI) is a major public health problem. Cold winter weather increases the risk of AMI, but factors influencing susceptibility are poorly known. We conducted an individual-level case-crossover study of the associations between winter cold spells and the risk of AMI, with special focus on survival at 28 days and effect modification by age and sex. All 16,071 adult cases of AMI among the residents of the city of Kaunas in Lithuania in 2000–2015 were included in the study. Cold weather was statistically defined using the 5th percentile of frequency distribution of daily mean temperatures over the winter months. According to conditional logistic regression controlling for time-varying and time-invariant confounders, each additional cold spell day during the week preceding AMI increased the risk of AMI by 5% (95% CI 1–9%). For nonfatal and fatal cases, the risk increase per each additional cold spell day was 5% (95% CI 1–9%) and 6% (95% CI − 2–13%), respectively. The effect estimate was greater for men (OR 1.07, 95% CI 1.02–1.12) than for women (OR 1.02, 95% CI 0.97–1.08), but there was no evidence of effect modification by age. Evidence on factors increasing susceptibility is critical for targeted cold weather planning.